2020
DOI: 10.1177/2167479519897288
|View full text |Cite
|
Sign up to set email alerts
|

“My Story Is My Activism!”: (Re-)Definitions of Social Justice Activism Among Collegiate Athlete Activists

Abstract: Despite the recent re-emergence of the athlete activist into public consciousness, activism among athletes continues to be viewed as nonnormative behavior. Drawing from interviews with 31 National Collegiate Athletic Association Division I collegiate athlete activists from across the United States, this study examined contemporary definitions of collegiate athlete activism for advancing social justice efforts. Five different conceptualizations of social justice activism emerged during the interviews: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Mentoring, or a relationship where a more experienced individual guides, teaches, and molds less experienced individuals (Rhodes et al, 2006), was critical to influencing athletes in how they could impact change, helping them overcome challenges, and providing validation for their own thoughts and actions. The importance of mentors is not surprising as mentors can provide a guiding perspective to those with less experience and can be especially important during the formative years of college (e.g., Eby et al, 2008; Kluch, 2020). Additionally, some athletes cited mentors who were white, but frequently mentors were racially minoritized individuals who supported them even though they might not have shared the same racial or ethnic identities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentoring, or a relationship where a more experienced individual guides, teaches, and molds less experienced individuals (Rhodes et al, 2006), was critical to influencing athletes in how they could impact change, helping them overcome challenges, and providing validation for their own thoughts and actions. The importance of mentors is not surprising as mentors can provide a guiding perspective to those with less experience and can be especially important during the formative years of college (e.g., Eby et al, 2008; Kluch, 2020). Additionally, some athletes cited mentors who were white, but frequently mentors were racially minoritized individuals who supported them even though they might not have shared the same racial or ethnic identities.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the lack of white mentors might put an additional burden on racially minoritized coaches and community leaders to mentor athletes in an already exhausting space that can increase the risk of burnout (Chen & Gorski, 2015). Because mentorship can be a form of activism for college athlete activists (Kluch, 2020), white athlete activists should provide mentorship to other white athletes navigating racial justice work. Practitioners, educators, administrators, and other staff members in higher education, both within and outside of athletics, should create specific programming for white athletes to develop mentorships skills, so that the emotional labor attached to mentorship can be taken off racially minoritized peers and shifted more toward those holding privileged racial identities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Havana McElvaine, a collegiate athlete who kneeled to protest police brutality, indicated her coach's support was one reason for her actions (University of Washington, 2017). Similarly, Kluch (2020) found that athletes draw heavily from mentorship in their activism. Conversely, several athletes who acted without support of their coaches or individuals at their institution faced backlash that included loss of playing time and scholarship, and even suspension or removal of the team (Kaufman, 2008).…”
Section: Social Support For Activismmentioning
confidence: 99%
“…In this most recent new wave of social justice athlete activism led by Black athletes (Edwards, 2016), activist efforts can take multiple forms including, but not limited to, community outreach, financial contributions, public statements, wearing activist apparel (e.g., "I can't breathe" shirts), and engaging in protests or other public displays of resistance (Mac Intosh et al, 2018). While these efforts have often taken place at the professional level, collegiate athletes have increasingly used their position on college campuses to encourage political and social change as well (Kluch, 2020). For example, in 2015, the University of Missouri's team protested discriminatory practices and racist actions on their campus (Ferguson & Davis, 2019;Yan et al, 2018) and football players at Northwestern University led an unsuccessful attempt to unionize (Strauss, 2015).…”
mentioning
confidence: 99%
“…Given sport is a microcosm of society (Coakley, 2015), it is not surprising that conversations surrounding racial injustice and systematic racism would (once again) permeate the sports arena. Increases in social activism within sport (see e.g., Cooper et al, 2019;Kluch, 2020) brought a level of uncertainty for sport organizations as most wrestled with how to properly handle the social justice climate during the summer of 2020 (Evans et al, 2020a). For example, in the National Basketball Association (NBA), following a video release of the Jacob Blake shooting, for the first time ever in NBA history, players from the Milwaukee Bucks decided to forego their game that night to stand in solidarity with those fighting for social justice.…”
Section: Introductionmentioning
confidence: 99%